ELTV Channel 6 News (African Knowledges and the History Publication since the 1970s)
Broadcasting on elections of National Chairs at the National Democratic Party of Liberia (NDPL) convention; annex of high school named after President Samuel Kanyon Doe.
Keywords: Politics; Local News